Metastable phase formation during solidification of undercooled melt - Ojha S.N. (My University, 2025)
Undercooling behaviour of micron-sized droplets entrained in the matrix of the primary phase of Ag-Ge, Al-Ge and Cu-Ag alloys was investigated. Thermal cycle consisted of equilibration of hypoeutectic alloys above the eutectic temperature in two phase liquid-solid region followed by their slow cooling or quenching from the mushy state. Repeated thermal cycling generated a wide size range of droplets. During slow cooling droplets exhibited a large undercooling below the eutectic temperature of alloys. Solidification structure of the undercooled droplets revealed presence of metastable phases in Ag-Ge and Al-Ge alloys and a non-equilibrium solid solution phase in Cu-Ag alloy. Solidification behaviour of undercooled melt and formation of metastable microstructure are discussed. © 2001 Elsevier Science B.V. All rights reserved.